Witów, zespół klasztorny OO. Norbertanów, gm. Sulejów, woj. łódzkie (Informator Archeologiczny: Badania, 1999)
Keywords: witów

Średniowieczne dzieje klasztoru norbertanów w Witowie - Kędzierska, Małgorzata (Nasza Przeszłość, 1996)
The monastery in Witów near Piotrków Trybunalski was built before 1185 by the bishop of Płock, Wit (Vitus) from Chotla. Some time later, his brother Dzierżko (Derslaus) founded a monastery in Busko. Legal rights made both monasteries dependent on the founder's family. Initially, Witów was probably a double foundation, for both monks and nuns, living according to the adapted Augustinian rule. At the turn of the first decade of the 13th century, Augustinian canons in Witów adopted the Rule of St. Norbert and Premont's obedience. Despite the relatively small assets of the monastery and the destruction that was probably caused by the Tatar invasions in 1241, the foundation managed to survive. Church sources from the end of the 13th century again mention the monastery in Witów and the associated nickname of the sisters in Busko. In the 13th–15th centuries, the monastery's income gradually increased, which was to some extent due to successful disputes with the Cistercians in Sulejów. In the 15th century, Witów successfully competed for control with the fraternal foundations of Wrocław and Brzesko over the monasteries of Norbertine nuns in Lesser Poland. Until the end of that century, Witów controlled the settlements in Busko and Płock and the neighboring parish of Krzyżanowice, which provided additional income.
Keywords: witów

Kościół i plebania w Witowie pod Piotrkowem - Jaskulski, B. (Kronika, 1909)
Keywords: witów

Destruction de l'Abbaye de Witow 1241 - Slupnicka, Sr. Caroline (Revue de l'Ordre de Prémontré et de sa mission, 1908)
Keywords: witów